Progress and Perspective of High‐Entropy Strategy Applied in Layered Transition Metal Oxide Cathode Materials for High‐Energy and Long Cycle Life Sodium‐Ion Batteries - Wang, Lei; Wang, Leilei; Wang, Haichao; Dong, Hanghang; Sun, Weiwei; Lv, Li‐Ping; Yang, Chao; Xiao, Yao; Wu, Feixiang; Wang, Yong; Chou, Shulei; Sun, Bing; et al. (Advanced functional materials, 2025)
Layered transition metal oxide (LTMO) cathode materials of sodium‐ion batteries (SIBs) have shown great potential in large‐scale energy storage applications owing to their distinctive periodic layered structure and 2D ion diffusion channels. However, several challenges have hindered their widespread application, including phase transition complexities, interface instability, and susceptibility to air exposure. Fortunately, an impactful solution has emerged in the form of a high‐entropy doping strategy employed in energy storage research. Through the implementation of high‐entropy doping, LTMOs can overcome the aforementioned limitations, thereby elevating LTMO materials to a highly competitive and attractive option for next‐generation cathodes of SIBs. Thus, a comprehensive overview of the origins, definition, and characteristics of high‐entropy doping is provided. Additionally, the challenges associated with LTMOs in SIBs are explored, and discussed various modification methods to address these challenges. This review places significant emphasis on conducting a thorough analysis of the research advancements about high‐entropy LTMOs utilized in SIBs. Furthermore, a meticulous assessment of the future development trajectory is undertaken, heralding valuable research insights for the design and synthesis of advanced energy storage materials. Layered transition metal oxides (LTMOs) are promising candidates for sodium‐ion batteries (SIBs). However, their widespread use is hindered by complex phase transitions, slow dynamics, and low stability. This review introduces high‐entropy materials, detailing their origins, definitions, and advantages for energy storage by stabilizing the layered structure, reducing ionic transport barriers, and enhancing redox reaction stability, and then it concludes with prospectives for advancing high‐entropy materials to develop high‐performance SIBs.